A Case of Preeclampsia with Uterine Necrosis after Uterine Artery Embolization for Postpartum Hemorrhage. (17th May 2022) - Yoshikawa, Midori; Seyama, Takahiro; Iriyama, Takayuki; Sayama, Seisuke; Fujii, Tatsuya; Toshimitsu, Masatake; Nakaya, Moto; Kurokawa, Ryo; Shibata, Eisuke; Watadani, Takeyuki; Kumasawa, Keiichi; Nagamatsu, Takeshi; et al.
Abstract : Uterine necrosis is a rare complication in uterine artery embolization (UAE) for postpartum hemorrhage (PPH). Preeclampsia (PE) is a condition characterized with systemic endothelial damage and intravascular volume depletion. Whether a patient with PE is at high risk for uterine necrosis after UAE for PPH has been unknown. A 30-year-old primipara woman was diagnosed with PE based on hypertension and proteinuria during delivery. UAE was performed for PPH after forceps delivery. After UAE, the patient presented with pleural effusion and massive ascites as well as persistent fever unresponsive to antibiotics. Ultrasonography and contrast-enhanced magnetic resonance imaging (MRI) led to the diagnosis of uterine necrosis, for which we performed total laparoscopic hysterectomy. It should be kept in mind that patients with PE associated with massive ascites may be at high risk for uterine necrosis after UAE due to decreased uterine perfusion. Therefore, it is important to pay attention to persistent symptoms such as fever and abdominal pain after UAE to diagnose uterine necrosis.